2022
DOI: 10.1037/adb0000819
|View full text |Cite
|
Sign up to set email alerts
|

Do smokers’ harm perceptions of cigarillos differ by modified use of the tobacco product? Findings from waves 3 and 4 of the PATH study.

Abstract: Objective: The harm perceptions of individuals who smoke either blunts or the Black & Mild (B&M) brand, which is often "freaked," have seldom been investigated. Since these practices could affect users' perceived health risks of the cigarillo, this study was intended to compare such risks among cigarillo users by modified use of the tobacco product. Method: Adult cigarillo and blunt smokers were selected from the Population Assessment of Tobacco and Health Study for cross-sectional (Wave 4; n = 3,331) and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…33 34 Many of these issues around warning noticeability could also apply to cigarette and other tobacco packaging, yet in this context, they highlight concerns about the inconsistent application of cigar warnings and the need for uniform regulations like those applied to cigarettes. Recent survey research has found high cigarillo harm perceptions among users who more frequently noticed warnings, 13 but relatively low levels of noticing cigarillo warnings. 35 Despite overall inattention to warnings, participants across groups supported the use of PWLs on cigarillo packaging, even stating they were drawn to PWLs they previously encountered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 34 Many of these issues around warning noticeability could also apply to cigarette and other tobacco packaging, yet in this context, they highlight concerns about the inconsistent application of cigar warnings and the need for uniform regulations like those applied to cigarettes. Recent survey research has found high cigarillo harm perceptions among users who more frequently noticed warnings, 13 but relatively low levels of noticing cigarillo warnings. 35 Despite overall inattention to warnings, participants across groups supported the use of PWLs on cigarillo packaging, even stating they were drawn to PWLs they previously encountered.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA has emphasised the importance of warning labels as a policy mechanism to promote product awareness and knowledge of risks 31. While strengthening label standards may include strategies to improve attention to them, it may also entail the development of additional warning message statements to improve knowledge,32 and/or more tailored versions of existing ones 13 29. For example, even a slight adjustment to the current FDA recommended nicotine warning to explicitly include the wrapper (eg, ‘This product, including the wrapper, contains nicotine…’) may be useful to address uncertainty and increase basic knowledge about cigar/cigarillo wrappers, which are made from tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation